Hyponatremia as drug-induced or secondary to endocrine disorder electrolyte abnormality - Ewa Tywanek; Paulina Trojanowska; Jakub Wronecki; Agnieszka Zwolak; Robert Jan Łuczyk (Kazimierz Wielki University, 2019)
Introduction: Hyponatremia is one of the most commonly occuring electrolyte disorder. The main clinical symptoms of natrium imbalance are weakness, lost of appetite, headache, nausea with or without vomiting or altered mental status with somnolence or even seizures and death. Purpose: To present a list of drugs pretending to occurrence or natrium serum level reduction and known endocrine disorder causing hyponatremia. Summary: Hyponatremia is very common electrolyte disorder. Changes that may develop in human organism in the presence of this type of dyselectrolytemia, may be extremely dangerous for proper functioning and life of the entity. It's well known, that hyponatremia may be caused by multiple factors, such as hormonal disturbances, taking special medicines or even excessive physical activity. It may also develop due to popular health conditions, for example congestive heart failure, liver cirrhosis, malignancies, neurological disorders or human-immunodeficiency virus infection1⁠. The huge amount of patients that are hospitalized in Chair and Department of Endocrinology in Lublin has prompted us to right analysis, due to available medical literature - the endocrine causes of hyponatremia. In second part of this review paper we aimed to enumerate drugs, that are able to result in developing hyponatremia.